2013
DOI: 10.1097/ta.0b013e3182788b5a
|View full text |Cite
|
Sign up to set email alerts
|

High-volume trauma centers have better outcomes treating traumatic brain injury

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 5 publications
1
29
0
Order By: Relevance
“…The lower SMR may be interpreted as an indicator of the quality of performance, although one should keep in mind that these systems potentially might overestimate the mortality rate and need to be recalibrated for updated data and for trauma patients before such conclusion can be made. Additionally, several studies reported a positive correlation with a strong association between trauma volume centre and outcomes of trauma patients with significant improvements in mortality when volume exceeds 650 cases per year [30][31][32]. The high volume, more than a 1000 trauma cases every year, may have been potentially a contributing factor to the improved primary outcome in our abdomino-pelvic trauma patients.…”
Section: Discussionmentioning
confidence: 90%
“…The lower SMR may be interpreted as an indicator of the quality of performance, although one should keep in mind that these systems potentially might overestimate the mortality rate and need to be recalibrated for updated data and for trauma patients before such conclusion can be made. Additionally, several studies reported a positive correlation with a strong association between trauma volume centre and outcomes of trauma patients with significant improvements in mortality when volume exceeds 650 cases per year [30][31][32]. The high volume, more than a 1000 trauma cases every year, may have been potentially a contributing factor to the improved primary outcome in our abdomino-pelvic trauma patients.…”
Section: Discussionmentioning
confidence: 90%
“…Finally, the low in-hospital and 5-year mortality rates observed in patients treated by surgeons who had performed a high volume of TBIs in the previous year and the positive association observed between TBI outcomes and volume of surgeries performed by the surgeon and by the hospital in the previous year are consistent with those in other longitudinal studies. 21,24 In the current study, the trend analysis of TBI reveals increasing hospital resource utilization, decreasing in-hospital mortality, and an increasing temporal trend in the prevalence of TBI, especially in elderly patients. All 3 trends were simultaneous and consistent over time.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have shown that in an analysis within level I centers only, a driving force that determines survival is volume and as trauma center volume increases the odds of mortality decrease. 2, 19 A possible explanation for our data not showing a 24-hour survival advantage in level I designated centers may be related to findings in the original study. In the original study reported by Bulger 10 there was a higher mortality in the hypertonic saline cohorts in the subgroup of patients who did not receive blood transfusions in the first 24 hours, compared to the control group receiving normal saline.…”
Section: Discussionmentioning
confidence: 69%
“…Many of these studies rely on administrative datasets, 5, 18, 19 statewide registries 8, 2022 or the National Trauma Data Bank (NTDB) 2, 7, 9 where accuracy and validity of data has been questioned. 2325 An advantage of this study is that it is based on prospectively collected data with quality control and review and does not rely on administrative datasets or registry downloads.…”
Section: Discussionmentioning
confidence: 99%